Peningkatan Hasil Belajar Matematika melalui Pembelajaran Metode Discovery Learning - Nurfaida Tasni (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2017)
This research is Classroom Action Research aimed at improving students mathematics achievement of Class VIIIA Students of SMP Negeri 10 Bulukumba through the implementation of discovery learning method. The subject of the research were Class VIIIA Students of SMP Negeri 4 Bulukumba. The study was conducted within two cycles. The first cycles was conducted for 4 lessons and the second cycles for 5 lessons. Data were gathered using mathematics achievements test in each final of cycle according the matherial that is taught. Data were then analyzed by employing both qualitative and quantitative analyses. From descriptive analysis show that: (1) Within the first cycle, the students average score reached in the achievement test was 56,83; which was categorized as being in moderate level. Within the second cycle with the correction based on the reflection from the first cycle, there was an improvement of the mathematics achievement of student become 79,98; which was categorized as being in high level. (2) Students were more active in the process of teaching and learning. Beside happened improving mathematics achievement in each cycle caused: (1) The students more the more active forward in front of the class to doing question, improved from 16,9 % become 49 %. (2) The students were the more ask at the implementation happens improved from 15 % become 23 %. (3) The students are doing their homework improved from 57,5 % become 89,5 %. According the analysis data above, it could be concluded that the mathematics achievement of Class VIIIA Students of SMP Negeri 10 Bulukumba improved after the implementation of discovery learning method.